Analytical, Theoretical and Experimental Investigation of Linear Viscoelastic Thin Plate Deflection with Two Edges Fixed and the Other Two Edges Simply Supported - J. Jweeg, Muhsin; K. Radi, Samira; Kh. Hussein, Sabah (Journal of Engineering and Sustainable Development, 2007)
A polyester and composite polyester thin plate have been tested under a certain constant distributed load (q=8N/mm2) so as to give a linear behavior over the plane of area at constant temperature (T=15ºC). The plate has been tested for thickness values (t=2,3,4mm). The type of boundary condition used here is two sides are fixed and the other two sides are simply supported. For the linear behavior of the polymer, a linear finite element program is achieved with the aid of FORTRAN power station program. The results of the FEM, theoretical and the experimental were compared. A good accuracy has been observed between the FEM, theoretical and the experimental work. In general the deflection behavior depends on the creep compliance. Increasing thickness results in decreasing the deflection, this decreasing depend on the value of thickness increasing. The deflection rate decrease during time for polyester, which depend on the creep function. The increasing in the plate dimensions ratio results in increasing the plate surface deflection for both plates (polyester and composite polyester plate). A composite plate shows a small increasing in the deflection during increasing the plate dimension ratio as comparing with that of polyester.